Effectiveness of Marriage Services Through Information System Management (SIMKAH) at Palu City Religious Court - Imam Muslih; Nurdin Nurdin; Marzuki Marzuki (State Institute for Islamic Studies Palu, 2020)
This paper discusses the effectiveness of marriage services through Marriage Management Information System (SIMKAH) at Palu city religious court. This study used qualitative research method. The data was collected through in-depth interview, observation, and document studies. The data was analyzed using grounded theory approach which begins with data reduction, presentation, analysis, and three level coding. The results show that the Marriage Management Information System (SIMKAH) has various purposes and functions. The marriage information system is used to anticipate data manipulation, and to facilitate a spouse in order to better understand how to register. The information system has been effectively used to serve couple who wants to marry. The system also reduce costs of marriage because it reduces time and registration cost.